The levels of Human Beta Defensin-2 (HBD-2) in premature neonates’ feces at Saiful Anwar Hospital, Malang, Indonesia - Eko Sulistijono; Putri Primawardani; Krisni Subandiyah; Anik Puryatni (Medical Faculty of Brawijaya University, Indonesia, 2022)
Background: Clinical evidence shows that the etiology of neonatal sepsis is translocation of the digestive tract of premature neonates. Human ß-defensor 2 has a protective effect during inflammation and apoptosis. This study aimed to determine the levels of fecal human ß-defensus-2 (HBD-2) as an inflammatory biomarker in premature neonates related to nutrition consumption. Methods: A cohort study design used in thirty-nine premature neonates according to inclusion criteria were collected in January to March 2019 in the neonatology room of RSUD Dr. Saiful Anwar Malang. The levels of premature neonatal feces HBD-2 were taken from all three sample groups on the seventh and fourteenth days and measured by the ELISA method. Data were analyzed using SPSS version 20 for Windows. Results: The mean levels of HBD-2 premature neonatal feces consuming formula milk alone were higher than other groups (349.16 + 67.66 vs 330.24 + 44.08 vs 215.65 + 51.34). There is a relationship between levels of HBD-2 premature neonatal feces with only breastfeeding (p=0,005; r=0.731), breast milk (p=0,005; r=0,727) and, formula milk only (p=0,003; r=0,761). Conclusion: The levels of HBD-2 in premature neonatal stools who consuming formula milk alone were significantly higher than levels of human HBD-2 premature neonatal stools that consumed only breast milk.